PENGARUH PEMBERIAN EDUKASI TERHADAP PENINGKATAN PENGETAHUAN IBU HAMIL TRIMESTER 1 TENTANG TANDA BAHAYA KEHAMILAN DI PUSKESMAS PANAMBUNGAN TAHUN 2024 - Rikhaniarti, Tri; Irmadani, Andi Syarifah; Arif, Nurlela (JURNAL KESEHATAN DELIMA PELAMONIA, 2024)
Background: Improving pregnant women's knowledge about danger signs during pregnancy is crucial to prevent complications that pose risks to both the mother and the baby. Objective: This study aims to evaluate the impact of educational interventions on enhancing the understanding of first-trimester pregnant women about pregnancy danger signs at Panambungan Health Center. Methods: The research employed a quantitative design with a pre-experimental approach involving pretest and posttest methods. The study sample consisted of first-trimester pregnant women selected using random sampling techniques. Educational interventions were conducted using questionnaires and interactive discussions. Results: The results showed a significant increase in the knowledge level of pregnant women after the educational intervention (p < 0.05). Conclusion: These findings indicate that appropriate education can enhance pregnant women's awareness of pregnancy danger signs, thereby preventing complications and improving maternal and fetal health. Therefore, it is recommended to strengthen routine educational programs in primary healthcare facilities such as health centers.